SMART PARKING SYSTEM 2 SLOT BERBASIS ESP32 - Muhammad Akram Haidar Syah; Aidil Syahputra Indardi; Nesty Aulia Hutagaol; Eka Dodi Suryanto; Dian Putra Saragi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid growth of motor vehicles has increased the demand for efficient and automated parking management systems. This study aims to design and implement a two-slot smart parking system based on the ESP32 microcontroller to detect parking availability and control vehicle access automatically. The system utilizes HC-SR04 ultrasonic sensors to detect vehicle presence and infrared sensors to validate vehicle movement at entry and exit gates. Servo motors are used to control the barrier gates, while LED indicators provide real-time parking status information. This research adopts an experimental approach including system design, hardware implementation, software development, and functional testing. The results show that the system successfully detects parking conditions, updates status in real-time, and controls vehicle access automatically with responsive and integrated performance. This system is effective as a prototype and has potential for further development into Internet of Things (IoT)-based applications.